Navigating cross-cultural experience of international students in traditional Chinese medicine universities: A qualitative exploration of learning, adaptation, and institutional support - Duo, Edward N; Lei, Pengding; Gao, Yazhuo; Zhu, Xuehua (Journal of International Students, 2026)
As China emerges as a leading destination for global higher education, its universities of traditional Chinese medicine (TCM) have seen a surge in international enrollment. This study aims to explore the learning experience of international students within such culturally embedded, discipline-specific institutions. Using purposive sampling, 20 international undergraduate students participated in semistructured interviews, which were analyzed using conventional content analysis. Three themes emerged: academic experiences, social experiences, and institutional support systems. While students valued integrated TCM-Western training, clinical exposure, and cultural exchange, they faced challenges related to language barriers, discipline-specific curriculum demands, and institutional support. International students in TCM universities experience both enrichment and strain during their cross-cultural and motivational adaptation process. Reforms emphasizing bilingual instruction, culturally responsive teaching, and enhanced student support could foster greater inclusion and engagement in China’s specialized higher education context.